Pelatihan dan Pendampingan Stimulasi Perkembangan Balita dengan Media Edukasi Permainan Ular Tangga bagi Kader Posyandu di Desa Karangtengah Kabupaten Banyumas: Training and Assistance for Stimulation of Toddler Development with Educational Media for Snake and Ladder Games for Posyandu Cadres in Karangtengah Village, Banyumas Regency - Hapsari, Wanodya; Yuliani, Diki Retno; Winarso, Septerina Purwandani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Early age is a golden age, an opportunity and a critical period for children's development. Early stimulation is very necessary by children as a stimulus for aspects of their development. The role of posyandu cadres is needed in conducting counseling on toddler parenting, stimulation, early detection of growth and development so that children grow healthy, active, intelligent and responsive. Community Service was held on Friday, August 30, 2024 at the LEM Hall of Karangtengah Village, Baturraden, Banyumas. This activity is the Training and Assistance for Stimulation of Toddler Development with Educational Media for Snake and Ladder Games for Posyandu Cadres in Karangtengah Village, Banyumas Regency, carried out by 3 lecturers, 3 students with lectures, discussions and practice methods so that they can provide developmental stimulation for toddlers. The target is Posyandu cadres in Karangtengah Village, Baturraden, totaling 30 people. The evaluation carried out was a question and answer and posttest which was carried out after the activity was completed. Overview of the implementation: opening, remarks by the midwife of Karangtengah Village, remarks by the head of the Community Service team, pretest, material delivery, discussion, rest, practice of Stimulation of Toddler Development with Educational Media of Snake and Ladder Games, posttests, closing. The results of the training were obtained by cadres before participating in the training was good knowledge of 16.7%, while for sufficient knowledge of 70% and lack of 13.3%. The knowledge of cadres after participating in the training is good knowledge of 56.7% and 43.3% have sufficient knowledge.